2020
DOI: 10.1016/j.jaci.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of IL-6 and CRP predict the need for mechanical ventilation in COVID-19

Abstract: Background: Coronavirus disease 2019 (COVID-19) can manifest as a viral-induced hyperinflammation with multiorgan involvement. Such patients often experience rapid deterioration and need for mechanical ventilation. Currently, no prospectively validated biomarker of impending respiratory failure is available. Objective: We aimed to identify and prospectively validate biomarkers that allow the identification of patients in need of impending mechanical ventilation. Methods: Patients with COVID-19 who were hospita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

71
803
5
25

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 926 publications
(947 citation statements)
references
References 34 publications
71
803
5
25
Order By: Relevance
“…This is consistent with our ndings in relation to CRP and IL-6 which were signi cantly higher in non-frail patients compared to frail patients; it is possible that frail older adults are not able to mount strong immune responses to COVID-19 infection due to immunosenescence [36]. Higher in ammatory responses to COVID-19 have been associated with severe disease and poorer outcomes [37], and dexamethasone, an immunosuppressant therapy, has been proven to reduce mortality in patients with COVID-19 requiring oxygen therapy or mechanical ventilation [38]. Therefore, if immune reactions differ in frail compared to non-frail older adults this may suggest the pathogenesis of COVID-19 differs by frailty and will have implications for the likely effectiveness of different treatments.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with our ndings in relation to CRP and IL-6 which were signi cantly higher in non-frail patients compared to frail patients; it is possible that frail older adults are not able to mount strong immune responses to COVID-19 infection due to immunosenescence [36]. Higher in ammatory responses to COVID-19 have been associated with severe disease and poorer outcomes [37], and dexamethasone, an immunosuppressant therapy, has been proven to reduce mortality in patients with COVID-19 requiring oxygen therapy or mechanical ventilation [38]. Therefore, if immune reactions differ in frail compared to non-frail older adults this may suggest the pathogenesis of COVID-19 differs by frailty and will have implications for the likely effectiveness of different treatments.…”
Section: Discussionsupporting
confidence: 91%
“…Model predictions were validated with clinical data from healthy humans and severe COVID-19 patients [34][35][36] . Figure 2A Subsequently, we focused on the clinically observed phenotypes of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…There is a substantial body of evidence linking the IL-6 concentration to the severity of disease and unfavorable outcome of Covid-19 [11,12,13,14,15,16,18,19,20]. However, to our knowledge, this study is the rst study which evaluated the ability of IL-6 to predict the need for supplementary oxygen administration as a surrogate marker of severe Covid-19 requiring hospital admission in the population of high risk elderly patients.…”
Section: Discussionmentioning
confidence: 97%
“…It also suggests clinical implications for intervention procedures for Covid-19 outbreak in LTCF. Han et al examined the predictive value of various cytokines and concluded that IL-6 is the best predictor of severe Covid-19 [16]. A metanalysis of 9 studies concluded that increased IL-6 is highly associated with severe disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation